IMPLEMENTATION OF WORK TRAINING CENTER STANDARDS IN UPT-LK REGION I RIAU PROVINCE IN 2018 (CASE STUDY OF PEKANBARU CITY WORK AREA) - Ranti Astari; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The quality of the workforce affects the absorption or adaptability of technology which also has an impact on economic growth. The increase in the quality and productivity of the workforce has not been maximized due to the limited training facilities and infrastructure that is owned, the limited quality of the quantity and quality of instructors according to the training needs and the limited information on the workforce needed. One of the functions of BLK is to absorb workers so that the unemployment rate in Pekanbaru City decreases. So, with this BLK, it is hoped that the workforce who do not have a job after participating in activities at BLK will have skills. The skills are those that can be used to find work, so unemployment will be minimal. However, the problem is that BLK is not effective because the employment of BLK alumni is still low.This study aims to see the implementation of the standards of the Work Training Center in UPT-LK Region I Riau Province, Pekanbaru City. This research uses descriptive research. The technique of selecting informants in this study was using purposive sampling technique. Data techniques are interviews and documentation.The results of the study found that the standard implementation of work training centers was not optimal. This is due to the fear of not fulfilling several elements of BLK implementation such as feasibility studies that do not meet standards, environmental analysis documents that do not meet standards, instructors and training personnel and facilities and infrastructure that do not meet BLK standards. From the research conducted, it was found that the implementation and program of BLK were still lacking. That is, it is like the training provided is not in accordance with the company demand for BLK graduates. Concerning the workforce of BLK graduates is still lacking. This is of course related to the learning methods applied by instructors in each field. Keywords: Work Training Center Standards, Feasibility Study, BLK Facilities and Infrastructure